2015
DOI: 10.1155/2015/385378
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Monocytic and Granulocytic Myeloid-Derived Suppressor Cells Subsets in Patients with Hepatitis C Virus Infection and Their Clinical Significance

Abstract: Myeloid-derived suppressor cells (MDSCs) have been shown to inhibit T-cell responses in many diseases, but, in hepatitis C virus (HCV) infected patients, MDSCs are still poorly studied. In this assay, we investigated the phenotype and frequency of two new populations of MDSCs denoted as monocytic and granulocytic MDSCs (M-MDSCs and G-MDSCs) in HCV infected patients and analyzed their clinical significance in these patients respectively. We found that the frequency of CD14+HLA-DR−/low cells (M-MDSCs) from HCV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
(29 reference statements)
2
26
1
Order By: Relevance
“…It will be important to determine whether different subsets of MDSCs (or other myeloid cells) infiltrate to different sites of infection or in response to different HSV species. (106,128).…”
Section: Dna Virusesmentioning
confidence: 99%
“…It will be important to determine whether different subsets of MDSCs (or other myeloid cells) infiltrate to different sites of infection or in response to different HSV species. (106,128).…”
Section: Dna Virusesmentioning
confidence: 99%
“…A study by Nonnenmann et al [38] reported that peripheral MDSCs were not significantly increased in patients with chronic HCV infection, and there was no difference in MDSC based on genotype or viral load, and a similar effect was found for suppression the function of CD8 + T cells. In another study, mMDSCs were observed to be unrelated to HCV RNA loads, and levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) [39].…”
Section: Discussionmentioning
confidence: 96%
“…The discrepancy might be explained by the differences in viral factors among different viral isolates or virally derived factors in generation and accumulation of MDSCs over the course of infection, or even by the influence of host genetic background and/or environmental differences. In this regard, Ning et al [39] reported that the frequency of mMDSCs in HCV infected patients had certain relevance with age, where patients older than 40 years old group had a significantly higher frequency of mMDSCs than that of age less than 40 years old group. In our study, however, we found that the frequency of gMDSCs was significantly higher in male than that in female HBV infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75][76][77] One study reported that M-MDSCs (CD14 + HLA-DR −/low ), but not G-MDSCs (HLA-DR −/low CD33 + CD11b + CD15 + ) from blood of HCV-infected subjects increased considerably in comparison with healthy controls. 78 Similarly, M-MDSCs increase significantly in blood of HIV/HCV-coinfected patients. 79 As in HIV, the viral HCV core protein (HCVc) could be involved in the induction of MDSC proliferation.…”
Section: Viral Infectionsmentioning
confidence: 98%
“…Several studies have reported an increase in MDSC levels in subjects positive for HCV . One study reported that M‐MDSCs (CD14 + HLA‐DR −/low ), but not G‐MDSCs (HLA‐DR −/low CD33 + CD11b + CD15 + ) from blood of HCV‐infected subjects increased considerably in comparison with healthy controls . Similarly, M‐MDSCs increase significantly in blood of HIV/HCV‐co‐infected patients …”
Section: The Key Role Of Mdscs During Bacterial Viral and Parasiticmentioning
confidence: 99%